2009
DOI: 10.1177/0022167809341996
|View full text |Cite
|
Sign up to set email alerts
|

Transforming From Cocoon to Butterfly: The Potential Role of the Body in the Process of Posttraumatic Growth

Abstract: The diagnosis of cancer has the potential to elicit positive change (post traumatic growth [PTG]) through the experience of trauma and adversity. However, psychology and clinical practices and most recently positive psychology have been criticized for their indifference toward the influence of the body on positive psychological functioning. The aim of this study was to broaden the understanding of PTG, including its process and outcomes, using interpretive phenomenological analysis. Ten female breast cancer su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 48 publications
3
52
1
4
Order By: Relevance
“…Research with group physical activities has found that developing a positive support system, creating opportunities for disclosure, acting as sounding boards to help each other work through challenges, and role modeling ways to positively rebuild following breast cancer facilitate posttraumatic growth (Hefferon, Grealy, & Mutrie, 2008;Sabiston et al, 2007). The physical nature of exercise may also promote posttraumatic growth, as the body is both a focus of the trauma and fear of cancer, as well as a conduit of growth and renewal as one reconnects with the body during recovery (Hefferon, Grealy, & Mutrie, 2010). Indeed, tackling physical challenges together with other survivors may aid posttraumatic growth (Sabiston et al, 2007).…”
mentioning
confidence: 99%
“…Research with group physical activities has found that developing a positive support system, creating opportunities for disclosure, acting as sounding boards to help each other work through challenges, and role modeling ways to positively rebuild following breast cancer facilitate posttraumatic growth (Hefferon, Grealy, & Mutrie, 2008;Sabiston et al, 2007). The physical nature of exercise may also promote posttraumatic growth, as the body is both a focus of the trauma and fear of cancer, as well as a conduit of growth and renewal as one reconnects with the body during recovery (Hefferon, Grealy, & Mutrie, 2010). Indeed, tackling physical challenges together with other survivors may aid posttraumatic growth (Sabiston et al, 2007).…”
mentioning
confidence: 99%
“…Even though this is an effect due to treatment, in general women are tended to feel a personal responsibility for their weight gain (Tiggemann & Rothblum, 1997) as a result of control failure. This might be reinforcement as women in treatment may struggle with feeling less in control over their bodies (Hefferon, Grealy, & Mutrie, 2010) due to other changes in their body, such as mastectomy, lumpectomy, hair loss. Additionally, research suggests that for a significant portion of women, in the early months after being diagnosed with breast cancer, these body changes negatively affect bodyimage (Fobair et al, 2006).…”
Section: Breast Cancer Body Changes and Pamentioning
confidence: 99%
“…Serían así los estadios intermedios (II y III) los que generarían una incertidumbre y amenaza suficiente como para plantearse cambios vitales positivos y una perspectiva vital de poder realizarlos. En cuanto al tipo de tratamiento oncológico y el CPT la mayoría de estudios no encuentran relación significativa (e.g., Tallman, 2013), aunque tres muestran una relación directa entre recibir quimioterapia y desarrollar CPT (Hefferon, Grealy, & Mutrie, 2009;Jansen et al, 2011;Lee, Robin Cohen, Edgar, Laizner, & Gagnon, 2006;Lelorain et al, 2010). Finalmente, otras variables como el tiempo transcurrido desde el diagnóstico (Brunet, McDonough, Hadd, Crocker, & Sabiston, 2010), o el tratamiento oncológico (Turner-Sack, Menna, Setchell, Maan, & Cataudella, 2012) tampoco se han relacionado de forma fehaciente al CPT, aunque parece que el alejamiento temporal de la parte aguda de la enfermedad sí puede facilitar el CPT, sin determinarse claramente cuál sería el tiempo óptimo.…”
Section: Recurrenciaunclassified